Sistem Pengendali Lingkungan Greenhouse Dengan Wireless Sensor Network Untuk Mengoptimalkan Budidaya Hidroponik - Kevin Hartono; Henry Novianus Palit; Anita Nathania Purbowo (Jurnal Infra, 2022)
Hydroponic cultivation is currently widely used because its various advantages. However, it is undeniable that it still has shortcomings because environmental conditions need to be engineered to resemble the conditions of the original habitat. The problem that is in this treatment process is human limitations in terms of consistencyIn this thesis, a trial will be carried out to help make it easier for users to maintenance consistently by implementing Internet of Things (IoT) technology in hydroponic gardens for monitoring and control automatically and consistently, with using sensors installed in the reservoir to get reservoir conditions and relays to regulate the flow of electricity to control environmental conditions. Furthermore, android application was developed to make it easier for users to monitor and control the hydroponic environment. So, the result is a monitoring system that can take data on several parameters, as well as controlling environmental conditions automatically by flowing the controller fluid into the reservoir, and an Android application to access measurement data that has been done previously.